A eficácia de intervenções de alfabetização e leitura em crianças de 4-8 anos : uma revisão sistemática - Lindemann, Roberta (2020)
Reading promotes not only academical and professional qualification, but also provides the possibility of seeing oneself in the world and reflect about things 5 around. Reading importance is widely recognized, nonetheless, about 250 million children across the world are not acquiring basic reading and math skills, even though about 50% of them have spent at least four years in school (STONE et al., 2019). This study aims to do a systematic review, in order to investigate the efficacy of reading interventions which target literacy development with children aged from 4 to 8 years old who have dyslexia or are at risk. A search on databases was made, resulting in 710 papers, they were manually screened through the inclusion and exclusion criteria described in this paper´s methodology. When 30 papers were left, two judges screened one last time, and this resulted in 17 articles. The data were extracted and analyzed and are presented in this paper. There was no significant difference as to the content (phonological awareness, pre-literacy and literacy measures and reading skills) to demonstrate which content was responsible for a larger effect size. Concerning material and methods applied in the interventions (electronic or not, with a tutor or without), there was no significant difference, however, the mean effect size of curricular elements demonstrates more efficacy than the mean effect size of electronical material. In relation to the time of intervention, short to medium-term studies presented a correlational effect size in complex verbal ability, however long-term studies had a follow-up measuring for maintenance of effects, whereas short-term and medium-term studies have not presented such measuring.